MORPHOLOGICAL CHANGES IN THE MAJOR CEREBRAL VESSELS IN TREATED AND UNTREATED CEREBROVASCULAR DISEASES - Mamajonov B.S., Abduolimov A.A. , (Central Asian Journal of Medicine, 2025)
Cerebrovascular diseases typically follow a chronic course and involve pathological vascular changes such as stenosis, atherosclerosis, angiosclerosis, and occlusions. Among patients with these conditions, 72.6% undergo regular treatment, 13.6% receive irregular treatment, 6.52% receive non-etiotropic (symptomatic) treatment, and 7.28% remain untreated, often without even reporting symptoms. This observation is based on clinical and anamnestic data from deceased patients with cerebrovascular complications. Our study formed groups of treated and untreated patients based on clinical histories, revealing that these diseases predominantly affect individuals aged 45–59 and 60–74, as classified by WHO standards, rather than being evenly distributed across age groups.